Gambaran Penyesuaian Diri Warga Binaan Pemasyarakatan pada Sebuah Lapas Wanita di Indonesia - Zavelia Zuhriati Maghnina; Megah Andriany (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2020)
Introduction: Female inmates who newly admitted into prison has high stress level because she need to adapt with the environmental conditions, individuals, and rules that applicated in prison. In Indonesia there are no research about female inmates adjusment. The purpose of this study was to determine the description of female inmates adjustment in a female prison in Indonesia based the domains in the PAQ questionnaire and comparing the situation with outside of the prison.Methods: This was a quantitative research with descriptive survey and cross-sectional design. The sampling technique used n this research was total sampling with 46 respondents with criteria newly admitted into prison for 1-3 months. The sample criteria are able to write and read and willing to participate in the study. The data were collected using PAQ questionnaire. Results: The results of this study show that dominant domain that worse in prisons compare with outside prisons was comfort and sleep problems. The most dominant problem that female inmates needs is sports, privacy, and sleep. The majority of female inmates have good friends while in prison, never feel prison as home, and all female inmate understand the rules in prison. Conclusion: Nurses should provide nursing care to improve female inmates’ self-adjustment in order to prevent mental health problems.